SPONTANEOUS BACTERIAL PERITONITIS - Tutchenko, Mykola; Rudyk, Diana; Besedinskyi, Mykola; Chub, Sergey (Eastern Ukrainian Medical Journal, 2024)
Spontaneous bacterial peritonitis (SBP) is an infection of ascitic fluid, posing a severe complication in patients with portal hypertension (PH). Hospital mortality rates are exceedingly high, sometimes surpassing 85%. Only timely diagnosis and treatment can mitigate mortality and morbidity levels. Purpose. Through literature analysis and review, demonstrate the necessity, appropriateness, and efficacy of SBP treatment in patients with decompensated portal hypertension. Additionally, highlight the potential development of ascites and subsequent infections, which may not always be linked to liver cirrhosis. Materials and methods. This article conducts a literature review and assesses recommendations, findings from randomized controlled trials, meta-analyses, and other review articles published in databases such as PubMed, Scopus, Web of Science, and Google Scholar between 2000 and 2023. Outcome. Diagnostic paracentesis is recommended for all ascites patients requiring emergency care or hospitalization to ascertain SBP presence. Accurate differentiation between SBP and secondary bacterial peritonitis is crucial, as treatment approaches differ for each condition. Conclusions. Standard SBP treatment entails promptly administering broad-spectrum antibiotics, considering the potential for community-acquired or nosocomial SBP, and factoring in microbial antibiotic resistance. Given SBP’s annual mortality rate surpassing 50%, liver transplantation is recommended for SBP survivors.